Monitoring of total metal concentration in sludge samples: Case study for the mechanical–biological wastewater treatment plant in Velika Gorica, Croatia - Filipović, Josip; Grčić, Ivana; Bermanec, Vladimir; Kniewald, Goran (The Science of the total environment, 2013)
In this paper, monitoring of total metal concentration in sludge samples from wastewater treatment process is elaborated. The presented results summarize the analyses of sludge samples in a period from 2008 to 2012. Possible sources of pollutions are given. Primarily, waste solid samples were collected from different pretreatment steps: (A) coarse grid, (B) fine grid and (C) aerated sand grease grid. Samples of A and B followed a repeatable pattern in 2008 and 2010. According to the results from 2008, samples of C contained measurable concentration of the following metals (mg/kg dry matter): Zn (21), Ni (1.05) and Ba (14.9). Several types of sludge samples were analyzed: fresh raw sludge (PS; 6–12hour old), the sludge from the digester for anaerobic sludge treatment (DS; 48–72hour old), samples from lagoons where the sludge is temporarily deposited (DOS and DOSold; 30–120days) and sludge samples from agricultural areas (AA; aged over 180days). Additionally, samples of dehydrated sludge (DEHS and DEHSold; 90–180days) were collected upon construction of equipment for sludge dehydration in 2011. An analysis of total metal concentrations for Cu, Zn, Cr, Pb, Ni, Hg, Cd, Ba, As, Se, Sb, Co, Mo, Fe and Mn was performed by flame atomic absorption spectrometry (FAAS) and inductively coupled plasma-optical emission spectrometry (ICP-OES). The most recent results (year 2011) indicated a high concentration of heavy metals in PS samples, exceeding the MCLs (mg/kg dry matter): Cu (2122), Zn (5945), Hg (13.67) and Cd (6.29). In 2012 (until July), only a concentration of Cu exceeded MCL (928.75 and 1230.5 in DS and DEHS, respectively). A composition of sludge was variable through time, offering the limited possibility for future prediction. The sludge is being considered as a hazardous waste and a subject of discussion regarding disposal. ► Summarized 5-year monitoring data for heavy metals in sludge ► Partially determined sources of pollution by heavy metals ► Detected shortcomings in national legislative ► Performance of MBWT in given circumstances is discussed.